In situ treatment of juvenile frogs for disease can reverse population declines. Issue 9 (7th July 2022) - Cook, Kimberly; Pope, Karen; Cummings, Adam; Piovia‐Scott, Jonah
Abstract: Effective management of wildlife populations threatened by disease requires accurate predictions about the consequences of intervention. However, generating such predictions is challenging, especially for organisms with complex life histories that are also threatened by climate change, such as montane amphibians. Cascades frogs ( Rana cascadae ) in northern California have experienced dramatic declines associated with the fungal pathogen Batrachochytrium dendrobatidis ( Bd ), and remnant populations are also threatened by changing climate conditions. We evaluated the population‐level impacts of treating Cascades frog metamorphs with the antifungal chemical itraconazole using a field experiment and population simulations. We explored the influence of larval habitat on these treatment effects by including metamorphs from different larval habitat types. We found that frogs treated with itraconazole were more than four times more likely to survive their first winter than untreated controls and had reduced Bd infection intensity compared to other surviving frogs from the same cohort in the following year. We also found an effect of larval habitat type on Bd infection in recently metamorphosed frogs, with the lowest levels of infection occurring in frogs emerging from larval habitats that tend to be intermediate in temperature and drying rate. Applying the differential apparent overwinter survival of treated and untreated metamorphs to population projections suggests that intermittent antifungal treatment of metamorphs has the potential to restore population viability. Our results indicate that in situ treatment of individual hosts may be a useful component of a comprehensive management strategy to reduce the risk of pathogen‐mediated population declines and extirpations. Abstract : Effective management of wildlife populations threatened by disease requires accurate predictions about the consequences of intervention. We evaluated the population‐level impacts of treating frogs threatened by the fungal disease chytridiomycosis with an antifungal chemical using a field experiment and population simulations. Our results indicate that in situ treatment of individual hosts may be a useful component of a comprehensive management strategy to reduce the risk of pathogen‐mediated population declines and extirpations.